Mendorong Evaluasi Diri Retrospektif Positif Mahasiswa dengan Implementasi Strategi Motivasi - Irma Soraya; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2021)
This research discusses a study on the motivational strategies employed by instructors to inspire English Language Education students at UIN Sunan Ampel Surabaya, particularly focusing on the phase of encouraging positive retrospective self-evaluation. This qualitative study involved two instructors as research subjects, with student participation in the data collection process. Methods utilized included interviews, classroom observations, stimulated recall, and focus group discussions. Findings revealed that both instructors employed strategies of constructive feedback and recognition for students. However, one instructor did not showcase student work as a form of recognition. The use of the native language also played a role in the implementation of motivational strategies. The limitations of this study suggest that future research should explore other stages of motivational strategies and other factors influencing student motivation and instructor strategies.